Learning React : modern patterns for developing React apps / Alex Banks and Eve Porcello. - Banks, Alex (Software engineer); Porcello, Eve (O'Reilly Media, Inc., 2020)
Interested in React but find yourself confused about how to use it with the Flux architecture? This is your book. Authors Alex Banks and Eve Porcello show you how to build React applications with the entire React ecosystem, including Flux. You'll learn about the methodologies behind the creation of the library and its related tools through short interviews with key players in the React community. 'Learning React' is ideal for web developers and software engineers who understand how JavaScript, CSS, and HTML work in the browser, but have no prior understanding of React, functional JavaScript, Flux, or even advanced JavaScript.